English for Prospective English Teachers in Hong Kong: Classroom Language in English Lessons - Chi Wui Ng (Cranmore Publishing, 2021)
Informed by Critical Genre Analysis (CGA), an English for Specific Purposes (ESP) lesson on classroom language is designed for prospective English teachers in Hong Kong to assist them in demystifying their discursive performance in the professional context of English language classrooms in local schools and achieving pragmatic success in their professional practice of conducting English lessons. Needs of target learners are analyzed with respect to the professional culture, professional practice, and genres relevant to English teachers in Hong Kong. On the basis of the needs analysis, a recorded English lesson language is selected as an input material for the lesson and analyzed at textual, socio-cognitive, and socio-critical levels. Pedagogical procedures of the lesson embody genre analysis, generic transfer, and free genre production. After completion of the lesson, students' genre ownership, discursive performance, and competent specialist behaviour are expected to be assessed by means of a weblog recording prospective English teachers' discursive performance during their teaching practice in a local school.